PENGARUH PEMANASAN DAN PENAMBAHAN ETANOL PADA BAHAN BAKAR BENSIN TERHADAP TORSI DAN DAYA PADA SEPEDA MOTOR YAMAHA VEGA R TAHUN 2009 - Widodo, Ari (Jurnal Nosel, 2015)
Purposes of the research are to know effect of fuel heating in cylinder block and ethanol addition in gasoline on torsion and power of Motorcycle Yamaha Vega R 2009.The research is an experimental one. Sample is taken by using purposive sampling technique. Sample of the research is Motorcycle Yamaha Vega R 2009 with machine number MH34D72039J261872. Data of torsion and power is obtained by using dynotest Sportdyno V3.3. Data of the research is, first, data of torsion  and power without fuel heating and variation of ethanol and gasoline mixes are 0%, 5%, 10%, 15%, 20% and 30%; second, data of torsion and power with one-pipe fuel heating and variation of ethanol and variation of ethanol and gasoline mixes are 0%, 5%, 10%, 15%, 20% and 30%; third, data of torsion and power with two-pipe fuel heating and variation of ethanol and variation of ethanol and gasoline mixes are 0%, 5%, 10%, 15%, 20% and 30%; data of torsion and power with three-pipe fuel heating and variation of ethanol and variation of ethanol and gasoline mixes are 0%, 5%, 10%, 15%, 20% and 30%.Based on results of the research, it can be concluded that, first, the fuel heating either one-pipe, two-pipe, or three-pipe types can reduce torsion and power of motorcycle Yamaha Vega R 2009; second, ethanol addition of premium gasoline can reduce torsion and power of the motorcycle; third, the highest torsion of the tests, namely 8.913 N.m., was found for 0% ethanol addition without fuel heating, whereas the lowest torsion, namely 8.493 N.m., was found with variation of ethanol additions of 20% and 25% and two-pipe fuel heating; fourth, the highest power, namely 8.467 HP, was found with variation of ethanol additions of 0% and 5% without fuel heating, whereas the lowest power, namely 7.933 HP, was found with ethanol addition of 30% and two-pipe fuel heating.